HPLC Method Development and Validation for the Quantification of Related Impurities in Testosterone Cypionate Active Pharmaceutical Ingredient - Bharti, Amber; Kumbhare, Ravindra Motiram; Jeyaseelan, Christine (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim: The purpose of this research study, is to develop and validate a reverse phase HPLC test method for detecting relevant impurities in Testosterone cypionate (TCY). Materials and Methods: The chromatographic system for separation of related impurities were achieved in Zorbax XDB-C8 (15 cm x 4.6 mm), 5 micron HPLC column utilising gradient elution technique. Water was selected as solvent-A and Acetonitrile was preferred as solvent-B for mobile phase. The method is gradient technique. Column heater was kept constant at 35°C; the rate of flow was 1.2 mL per min; volume of injection was 20 μL and 240 nm was set for detector wavelength. Results: The % recovery was in the range of 95.6% to 108.7% for all impurities. The result of correlation coefficient were higher than 0.98. Testosterone is the major degradants obtained from forced degradation study. Conclusion: The created method can be utilise in quality control testing on a regular basis for the analysis of Testosterone cypionate.
Keywords: Testosterone cypionate; Testosterone replacement therapy; Male; hypogonadism; HPLC; Impurity profiling